Polymorphisms in Osteopontin Gene in Amazon Buffaloes - Rolim Filho, Sebastiao Tavares; Lobato Ribeiro, Haroldo Francisco; Ferreira de Camargo, Gregorio Miguel [UNESP]; Cardoso, Diercles Francisco [UNESP]; Aspilcueta-Borquis, Raul Rusbel [UNESP]; Tonhati, Humberto [UNESP]; Nunes, Kim de Borborema; Vale, William Gomes; Sousa, Keitiane Colares de; Eguchi Mesquita, Ellen Yasmin; Boaretto, Jose Luiz; Cardoso de Alcantara, Giselia de Lourdes (Int Buffalo Information Ctr, 2013)
The aim of this work was to identify polymorphisms in the osteopontin gene. It was used in this experiment 306 male buffaloes, older than 18 months, bred in two farms, one in the State of Amapa and the other farm in the State of Para. There was identified three SNP polymorphisms for the region amplified by the primer OS4 (5'upstream) and four SNP polymorphisms for the region amplified by the primer OS9 (exon 5 to exon 6). The polymorphisms were in positions 1478, 1513 and 1611 in the region amplified by OS4 and positions 6690, 6737, 6925 and 6952 in the region amplified by OS9. These data indicate that the osteopontin gene is important because it can have a substantial influence on the reproductive traits of male buffaloes.
Keywords: SNP; reproductive traits; Bubalus bubalis